1997
DOI: 10.1159/000150535
|View full text |Cite
|
Sign up to set email alerts
|

Infections of the Nervous System Caused by Varicella-Zoster Virus: A Review

Abstract: Varicella-zoster virus (VZV) is a cause of neurologic disease among humans. Both primary infection and recurrence may lead to neurologic infection and disease. Neurologic syndromes associated with acute VZV infection are caused by abnormal immune responses, the most frequent manifestation being cerebellar ataxia. Those associated with recurrences are often due to the direct effect of viral replication in the nervous tissue. VZV reaches the nervous system either through the bloodstream or by direct spread from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 78 publications
0
41
0
5
Order By: Relevance
“…More frequently CNS involvement occurs as a result of ADEM, a postinfectious, immune-mediated, predominantly demyelinating process. Both the direct and immune-mediated CNS effects of varicella need to be distinguished from Reye's syndrome (74,75).…”
Section: Viruses For Which Pcr Has Potential Efficacy In Diagnosis Bumentioning
confidence: 99%
“…More frequently CNS involvement occurs as a result of ADEM, a postinfectious, immune-mediated, predominantly demyelinating process. Both the direct and immune-mediated CNS effects of varicella need to be distinguished from Reye's syndrome (74,75).…”
Section: Viruses For Which Pcr Has Potential Efficacy In Diagnosis Bumentioning
confidence: 99%
“…In studies using nested PCR, it is suggested that VZV is an important etiological agent in acute aseptic meningitis (AAM) (11,17,18).…”
mentioning
confidence: 99%
“…4 There is no history of tick exposure and no ticks were found on exam, so we can rule out tick paralysis. Myelopathy associated with herpes zoster virus is rare in the absence of a rash, 5 and with a normal MRI and no fever, back pain, meningeal signs, or risk factors, both pyogenic meningomyelitis and epidural abscess are unlikely. There is no history of trauma, crush injury, snake bite, or industrial exposure, so we can rule out several diagnoses under the trauma and toxic heading.…”
Section: Faculty Discussionmentioning
confidence: 99%